Inovasi Kebijakan Pendidikan di Pemerintah Provinsi Jawa Barat - Syaiful Huda; Yogi Suprayogi Sugandi; Widya Setiabudi Sumadinata (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
In a country, the government has the responsibility to provide equitable and quality access to education for all its citizens. This involves policy and investment in the education sector, training teachers, developing relevant curricula, and building adequate educational infrastructure. The provision of education is a fundamental requirement for the reconstruction of a civilization. This is a basic service that every individual needs and a responsibility that must be carried out by the state. Therefore, education is the process of developing and imparting knowledge, skills, and values to individuals in order to improve their abilities and quality of life. Education does not only occur in the school environment but can also occur in the home, community, and surroundings. This study aims to explain and describe educational policy innovations in the Provincial Government of West Java by using policy innovation instruments to conduct analysis. The method used in this study is a descriptive qualitative approach with the determination of informants using purposive techniques and triangulation for data processing. The results of the analysis show that the concept of Jura Education is a policy innovation that has fulfilled three main instruments, namely regulatory instruments, economic and financial instruments, and soft instruments. However, as a pilot project, this policy innovation still encounters a number of challenges in its implementation, requiring development from the government and related actors.